Report of a Rare Case of Childhood Paratesticular Rhabdomyosarcoma (PT-RMS) and Literature Review - Pratiwi, Suci; Erlina, Nency (GoAcademica Research & Publishing, 2025)
Paratesticular rhabdomyosarcoma (PT-RMS) is a rare, aggressive soft tissue malignancy affecting children and adolescents. Early diagnosis and multimodal treatment are crucial to reduce recurrence and improve survival. We report a 6-year-4-month-old male with advanced PT-RMS presenting with a bleeding scrotal mass, severe malnutrition, and anemia. The patient had previously received 25 chemotherapy cycles and experienced relapse, requiring reinitiation of chemotherapy with vincristine, actinomycin C, and cyclophosphamide. Imaging revealed an extensive fixed mass involving the scrotum, penis, bladder wall, and enlarged inguinal and para-iliac lymph nodes. Multidisciplinary management included supportive care, wide excision, and planned bilateral inguinal lymph node dissection. This case highlights the diagnostic and therapeutic challenges of advanced PT-RMS, emphasizing the role of proper imaging, radical surgery with inguinal lymphadenectomy, and adjuvant chemotherapy to optimize local control and prevent metastasis. Effective management of pediatric PT-RMS requires timely diagnosis, complete surgical resection with lymph node evaluation, and adequate adjuvant therapy to improve outcomes and minimize recurrence risk.